Böses - Linde, Gesche (Zeitschrift für Theologie und Kirche, 2025)
The problem of evil is explored through philosophical, theological, and biblical perspectives in this article. It examines the phenomenological characteristics of what may be defined as evil, the relationship between evil and sin, the connection between evil and God, and the Christian approach to confronting evil.